2018
DOI: 10.1002/csr.1502
|View full text |Cite
|
Sign up to set email alerts
|

Improving CSR performance by hard and soft means: The role of organizational citizenship behaviours and the internalization of CSR standards

Abstract: This study analyzes 'hard' (i.e. formal structures) and 'soft' (i.e. values) determinants of corporate social responsibility (CSR) performance, such as the effectiveness of management systems for CSR and the role of managers' organizational citizenship behaviours. Based on a sample of 130 Italian organizations that adopted management systems according to an international standard, this study shows that CSR performance depends on employees' commitment and the internalization of formalized CSR practices. The stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 116 publications
2
52
0
1
Order By: Relevance
“…The study contributes to the emerging discussions on OCB related to environmental and social issues (Boiral & Paillé, ; Lülfs & Hahn, ; Testa, Boiral, et al, ). First, although the various drivers of OCBHSE have been investigated, a comprehensive assessment is still lacking.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The study contributes to the emerging discussions on OCB related to environmental and social issues (Boiral & Paillé, ; Lülfs & Hahn, ; Testa, Boiral, et al, ). First, although the various drivers of OCBHSE have been investigated, a comprehensive assessment is still lacking.…”
Section: Discussionmentioning
confidence: 75%
“…The evidence suggests that in the relation between OCB and HSE performance, workers' OCB makes the formal structures and systems more effective for HSE management, by facilitating the integration of formal procedures into daily operational practices (Boiral et al, ). OCB “lubricates” formal structures and management systems, providing the necessary proactivity and flexibility to push organizational improvement beyond mere compliance to procedures (Testa, Boiral, & Heras‐Saizarbitoria, ). Specifically, OCB allows organizations to maintain compliance with formal procedures and structures while pursuing performance improvements through the proactive and voluntary daily initiatives of the workers.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Hart and Milstein (1999) suggested that a lack of CSR-oriented ethical leadership in corporate management will be a disadvantage for promoting corporate CSR strategy. Other scholars further indicated that the impacts of institutional pressures on ethical leadership can be influenced by individual cognition, such as moral motivation (Hoque, Rahman, Molla, Noman, & Bhuiyan, 2018;Pan & Wei, 2014;Testa, Boiral, & Heras-Saizarbitoria, 2018;Tian & Liu, 2012;Wu et al, 2014). Furthermore, in promoting the development of corporate strategy, ethical leadership is also influenced by the corporate governance structure, such as managerial autonomy (Dill, 1958;Lioukas, Bourantas, & Papadakis, 1993;Li & Zhao, 2003;Xiao, 1991).…”
Section: Literature Reviewmentioning
confidence: 99%
“…First, in the research of revealing the prototype, the inconsistent results led scholars to explore the internal motivations from an ethical perspective. Brown and his colleagues deeply studied the influence of leadership on ethical behavior (Brown, Treviño, & Harrison, 2005;Trevino & Brown, 2004;Treviño, Brown, & Hartman, 2003;Trevino, Hartman, & Brown, 2000) and (Bogner & Barr, 2000;Nadkarni & Barr, 2008;Santos, Murmura, & Bravi, 2018;Testa et al, 2018;Wu et al, 2014).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation